An integrated study of glutamine alleviates enteritis induced by glycinin in hybrid groupers using transcriptomics, proteomics and microRNA analyses - He, Yuanfa; Dong, Xiaohui; Yang, Qihui; Liu, Hongyu; Zhang, Shuang; Xie, Shiwei; Chi, Shuyan; Tan, Beiping (Frontiers in Immunology, 2023)
Glutamine has been used to improve intestinal development and immunity in fish.We previously found that dietary glutamine enhances growth and alleviates enteritis in juvenile hybrid groupers (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatus♂). This study aimed to further reveal the protective role of glutamine on glycinin-induced enteritis by integrating transcriptome, proteome, and microRNA analyses. Three isonitrogenous and isolipidic trial diets were formulated: a diet containing 10% glycinin (11S group), 10% glycinin diet supplemented with 2% alanine-glutamine (Gln group), and a diet containing neither glycinin nor alanine-glutamine (fishmeal, FM group). Each experimental diet was fed to triplicate hybrid grouper groups for 8 weeks. The analysis of intestinal transcriptomic and proteomics revealed a total of 570 differentially expressed genes (DEGs) and 169 differentially expressed proteins (DEPs) in the 11S and FM comparison group. Similarly, a total of 626 DEGs and 165 DEPs were identified in the Gln and 11S comparison group.Integration of transcriptome and proteome showed that 117 DEGs showed consistent expression patterns at both the transcriptional and translational levels in the Gln and 11S comparison group. These DEGs showed significant enrichment in pathways associated with intestinal epithelial barrier function, such as extracellular matrix (ECM)-receptor interaction, tight junction, and cell adhesion molecules (P < 0.05). Further, the expression levels of genes (myosin-11, cortactin, tenascin, major histocompatibility complex class I and II) related to these pathways above were significantly upregulated at both the transcriptional and translational levels (P < 0.05). The microRNA results showed that the expression levels of miR-212 (target genes colla1 and colla2) and miR-18a-5p (target gene colla1) in fish fed Gln group were significantly lower compared to the 11S group fish (P < 0.05). In conclusion, ECM-receptor interaction, tight junction, and cell adhesion molecules pathways play a key role in glutamine alleviation of hybrid grouper enteritis induced by high-dose glycinin, in which miRNAs and target mRNAs/proteins participated cooperatively. Our findings provide valuable insights into the RNAs and protein profiles, contributing to a deeper understanding of the underlying mechanism for fish enteritis.